If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying T = (7 + RS) Remove parenthesis around (7 + RS) T = 7 + RS Solving T = 7 + RS Solving for variable 'T'. Move all terms containing T to the left, all other terms to the right. Simplifying T = 7 + RS
| T=(7+RS)forS | | -8+5u=-33 | | 8x+a-12=4x-13-5x | | 5t(9t+4)=0 | | s=4k+4 | | 8t+6=6+7t | | (4z+5)(3-z)=0 | | 13x+24x-31x=144 | | 7y+2=6y-2 | | 3x^2-12x-180=0 | | 3y+8=2y-6 | | 2x^2-6x+14=0 | | 3x^7-243=0 | | 2x+10y+(-10y)+(-10x)= | | 193.6=m(10000)+b | | 2b-15=-25 | | -x=.63 | | 2.2(h-5.3)=0 | | 4x-7+16=3x+12 | | 8(1+4x)+7=207 | | 27x+9y+36z= | | 5x^2-26y-24=0 | | (5+y)(5y-3)=0 | | 3(4j+5)=2(-10+5) | | x-.15x=510000 | | r=-0.691 | | (1+s)+1= | | 5x+4y=500 | | y=kx+fx | | 0.18-0.03(x+2)=-0.03(2-x) | | 5x+2=6+9x | | (3y-9)(-2y^2+7y+1)= |